Determination of wall width of gob-side entry driving by pre-built concrete wall and stress and deformation characteristics analysis - Lining GUO; Tianhe KANG; Jiachang WANG; Jie DENG; Ze WANG (Meikuang Anquan)
Aiming at the problem of determining the wall width of gob-side entry driving by the pre-built concrete wall, taking No.3 coal seam of Jinxing Coal Industry as the research background, the width range of the side wall is determined by theoretical calculation. Combined with numerical simulation, the stress distribution and deformation characteristics of the wall with different widths in the range are studied during the mining process of the working face. The width of the side wall is determined to be in the range of 0.43-2.41 m; the stress distribution and deformation characteristics of the wall with different widths are different numerically, but the dynamic change characteristics are roughly the same during the mining process of the working face; with the advance of the working face, the increase amplitude of the stress and deformation of the wall increases first and then becomes stable. Among them, the variation range is relatively large from 40 m ahead of the working face to 40 m behind the working face, and the variation range tends to be stable after 40 m behind the working face. With the increase of the wall width, the stress and deformation of the wall show a decreasing trend, and the change trend is significantly weakened when the wall width is 1.2-2.0 m. Combined with economic benefit factors, the wall width is determined to be 1.2 m.